Community-acquired pneumonia with an unusual radiographic pattern related to Lophomonas sp infection: case report - Alvarado-Castell, Huber; Caicedo-Solarte, William; Fernández-Chica, Dinno; Daza-Daza, Carlos; Salcedo-Badel, Lina; Sánchez-Bolívar, Martha; Maestre-Serrano, Ronald (Revista de Patologia Tropical / Journal of Tropical Pathology, 2025)
Lophomonas sp is a flagellated protozoan, described in the literature as a commensal in the digestive tract of insects such as cockroaches and termites. It has little association with the development of symptomatology in immunocompetent patients. However, a few cases of bronchopulmonary infections. Patient who started presenting respiratory symptoms focused initially like community-acquired pneumonia, with no response to empirical therapy following clinical management guidelines. It required a thorax tomography that evidenced alveolar occupation in an unusual pattern, leading to a Fiberoptic bronchoscopy plus bronchoalveolar lavage, achieving microbiological isolation of Lophomonas sp. Lophomonas pneumonia is a rare respiratory clinical picture. In case of slow-resolution pneumonia or one that does not respond to treatment, it is recommended to perform a new evaluation of the patient in their clinical history and request complementary diagnostic imaging to make it possible to reach a timely diagnosis and thus decrease mortality. KEY WORDS: Pneumonia; Lophomonas; cockroaches; Colombia